Parental Education in the Family according to Nusantara Tafsirs - Masykur, Masykur (Jurnal Iman dan Spiritualitas, 2025)
This article discusses the family-based character education model. This article specifically examines verses about important education in the family and analyzes the concept of important education in the family contained in the Tafsir An-Nur, Tafsir Al-Azhar and Tafsir Al-Misbah. This research is literature research that uses descriptive analysis methods, namely by collecting verses related to the topic of discussion and analyzing them, interpreting them with theories and references that support data analysis. This research found that it is important to pray to be given good offspring like the prophets and scholars. the importance of the role of parents in providing good examples, teaching monotheism, and creating an environment that supports the development of children's faith. According to them, parenting education is a process that includes teaching about patience, affection and respect for parents, especially when they are elderly. This is an integral part of a child's worship and responsibility in Islam.